A Comparative Analysis of Two English Coursebooks in Terms of Cultural Elements (Headway and English File) - Fakazlı, Özlem; Baytar, İlknur (Inonu University, 2021)
The current study aimed to do a comparative analysis of the cultural elements in two different English coursebooks (Headway and English File), which are commonly used for teaching English as a foreign/second language. With this purpose in mind, all the activities in Headway and English File were examined to find out how the cultural contents are represented. The study was designed as qualitative research, and the document analysis method was utilized as a data collection tool. The data collected in the coursebooks were evaluated through the content analysis method. As a result of the content analysis, it was revealed that more cultural elements were found in English File compared to the number of the cultural items found in Headway. Although the results varied, the study generally concluded that target cultural elements were dominant in two coursebooks. More specifically, target culture ranked the first, followed by international and local culture respectively in both coursebooks. To sum up, it was indicated that the elements of target culture were included more in these coursebooks. Based on the findings, it can be suggested that not only target culture but also other world cultures should be integrated into the coursebooks in order to enhance learners’ intercultural competence.
Keywords: 4. Education